Analysis of Community-Based Waste Management through Waste Bank in Tinjomoyo Urban Village, Semarang City, Central Java - Sarful Anam; Arum Siwiendrayanti (Universitas Diponegoro, 2023)
Waste is a problem that, until now, has been difficult for the Indonesian government to solve. The emergence of waste banks can make people aware of the need to manage waste properly. The community eventually became more educated about managing and sorting household waste. The household waste consists of used cardboard, used plastic drink bottles, used shoes, and other used items. If waste banks exist in a community and whether they have an impact on that community or other